Стратегічне управління сталим бізнесом у добу ESG: комунікаційний менеджмент як каталізатор системних змін - Ортіна, Ганна Володимирівна; Ortina, Hanna (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розкрито роль комунікаційного менеджменту як стратегічного інструменту трансформації бізнесу у контексті ESG-підходів та сталого розвитку. Здійснено аналіз типів комунікаційних практик (внутрішніх, зовнішніх, кризових) та їх впливу на формування ESG-репутації компаній. Запропоновано авторську ESG-матрицю комунікацій (Message–Channel–Impact) як засіб оцінювання прозорості, достовірності та адаптивності бізнес-повідомлень. Проведено системне картування за методом Influence Mapping для візуалізації ролі ключових стейкхолдерів у процесах стратегічного управління змінами. На основі кейс-стаді та дискурсивного аналізу ESG-звітів провідних компаній виявлено тенденції, наративи та прогалини в комунікації. У результаті розроблено сценарії ESG-комунікацій на період до 2050 року, що враховують глобальні ризики, ціннісні очікування суспільства та регуляторні вектори. Отримані результати можуть бути використані для формування стратегій комунікаційного супроводу трансформацій сталого бізнесу. /// EN: The article explores the intersection of office and communication management within the framework of modern professional ethics, highlighting their synergistic impact on organizational behavior and public administration. In the post-war and digitalization contexts, the role of ethical communication and managerial culture becomes increasingly vital for ensuring the resilience and sustainability of institutions. The authors present a systematic analysis of current approaches to office management and the strategic role of communication in fostering interpersonal trust, ethical climate, and effective decision-making in administrative structures. The study is based on a comparative analysis of Ukrainian and European professional standards, as well as empirical materials from public institutions. Particular attention is paid to the ethical dimensions of communication practices in office environments, including conflict management, team interaction, and decision-making transparency. The paper introduces structured tables illustrating key differences in communicative approaches and managerial ethics between domestic and European institutions. The research concludes that the integration of office and communication management through the prism of professional ethics leads to enhanced institutional efficiency, improved employee motivation, and a more transparent organizational culture. The article emphasizes the need for educational and professional development programs to reinforce ethical standards and communicative competence among public servants. The research also highlights the increasing relevance of value-based leadership and integrity-driven administration in shaping sustainable public institutions. The integration of office and communication management through the prism of professional ethics leads to enhanced institutional efficiency, improved employee motivation, and a more transparent organizational culture. The article emphasizes the need for educational and professional development programs to reinforce ethical standards and communicative competence among public servants.
Strategic management of sustainable business in the ESG era: communication management as a catalyst for systemic change
Keywords: стратегічне управління; сталий розвиток; ESG; комунікаційний менеджмент; корпоративна відповідальність; публічні наративи; системні зміни; office management; communication management; professional ethics; public administration; organizational culture; transparency; post-war recovery; European integration